2010
DOI: 10.1007/s10706-009-9300-1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Comparison of Crushed Aggregate and Recycled Pavement Material With and Without High Carbon Fly Ash

Abstract: In-place recycling of asphalt pavement materials is a sustainable rehabilitation method. Existing hot-mix asphalt (HMA) layer is pulverized and blended with some or the entire base course and possibly some subgrade to form a broadly graded material referred to as recycled pavement material (RPM). The RPM is then compacted as the new base course and overlaid by a new layer of HMA. In some occasions, additives are added to increase the strength of RPM base course, such as cement, emulsion, fly ash. It is plausib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 2 publications
3
28
1
1
Order By: Relevance
“…5a. The equation, CBR (%)=A*stabilizing agent (%)+B, was proposed in this study to predict the CBR of chemical-stabilized RAP specimens based on the test results obtained by Wen et al [33] and Cosentino et al [9]. The values of the parameters A and B obtained in this study are presented in Table 4.…”
Section: California Bearing Ratiomentioning
confidence: 89%
See 4 more Smart Citations
“…5a. The equation, CBR (%)=A*stabilizing agent (%)+B, was proposed in this study to predict the CBR of chemical-stabilized RAP specimens based on the test results obtained by Wen et al [33] and Cosentino et al [9]. The values of the parameters A and B obtained in this study are presented in Table 4.…”
Section: California Bearing Ratiomentioning
confidence: 89%
“…The values for the model parameters (K 1 and K 2 ) are presented in Table 3. Li et al [20] conducted M R tests at a deviatoric stress of 21 kPa on a 14-day-cured fly ash-stabilized RAP specimens while Wen et al [33] conducted M R tests at a bulk stress of 83 kPa on 7-and 14-day-cured fly ash-stabilized RAP specimens. They found that the M R increased with an increase in the fly ash content and the curing period as shown in Fig.…”
Section: Bulk Stress (Kpa)mentioning
confidence: 99%
See 3 more Smart Citations